High and volatile food prices: Drivers and impacts on food security in Eastern and Central Africa - Karugia, Joseph T. (International Livestock Research Institute, 2011)
This paper which draws from several reports and briefs that have been prepared by ReSAKSS in the last three years presents the results and major conclusions and recommendations from the analysis. (Executive summary available).